Conflict in Men’s Experiences With Antidepressants - Kerry Gibson PhD; Claire Cartwright PhD; John Read PhD (American Journal of Men's Health, 2018)
While men’s experiences of depression and help seeking are known to be shaped by gender, there is little research which examines their experience of using antidepressants to treat this. This study is based on in-depth, narrative-style interviews with 20 New Zealand men who had used antidepressants. The analysis identified a number of areas of conflict in the men’s accounts of using this medication. Conflict centered on the way taking antidepressants was seen as undermining personal control while also allowing users to take charge of their problems; facilitating general functioning while undermining sexual functioning; relieving emotional distress while undermining emotional vitality; and the tension participants felt between making autonomous judgments about the value of antidepressants and relying on the “expertise” of others. Participants negotiated these conflicts in a variety of ways. In some cases, antidepressants were positioned as being able to affirm aspects of traditional masculinity, while a smaller number of participants managed these conflicts by redefining aspects of their own masculinity in ways that contrasted with dominant constructions. This research is limited by the sample of older, more privileged men in the context of New Zealand culture which favors macho forms of masculinity. In similar contexts, mental health practitioners should be mindful of the conflicts that men might experience in relation to their antidepressant use. Facilitating men’s exploration of these issues may enable them to make better decisions about treatment options or to provide more effective support to those who have opted for antidepressant treatment.